Media Holding Company as a System: Genesis, State and Prospects of Development - MISONZHNIKOV, Boris Yakovlevich; TEPLYASHINA, Alla Nikolaevna; MELNIK, Galina Sergeevna; PAVLUSHKINA, Natalia Anatolievna; NIGMATULLINA, Kamilla Renatovna (Journal of Advanced Research in Law and Economics; Vol 6 No 2 (2015): JARLE Volume VI Issue 2(12) Summer 2015, 2016)
The work is aimed at revealing historical prerequisites and main trends of development of media holding companies as an objects system and as a method of media process organization. Various concepts and functioning schemes of media corporations have been analyzed and structural elements of media holding companies have been studied. Experience of leading international and Russian media concerns have also been analyzed. Dynamics of media complexes development is characterized by rapid expansion i.e. uptake of less powerful companies with more powerful and taking under control new territories. It has caused significant system errors. For example, great number of titles is concentrated in a few publishing houses, relatively small group of monopolists is extremely influential in production and distribution of media products. This group in fact dictates its rules for media market. The situation in Russia is even worse due to Federal Antimonopoly Service languid attempts, extremely high level of corruption and sophisticated system of lobbying of interests of a very small group of people close to the powers. The monopolization was made in the situation of catastrophically low level of media operation freedom, underdeveloped civil society, impoverishment of population and growing level of manipulation of the audience for the interests of an oligarchy clan.
Keywords: media holding company, media, system, media monopolization